Exposure to benzene and urinary concentrations of 8-hydroxydeoxyguanosine, a biological marker of oxidative damage to DNA. Issue 11 (November 1994) - Lagorio, S; Tagesson, C; Forastiere, F; Iavarone, I; Axelson, O; Carere, A
Abstract : OBJECTIVES--Benzene is an established animal and human carcinogen. The mechanism of benzene toxicity, particularly its leukaemogenic effect, is not fully understood. The modified base 8-hydroxy-deoxyguanosine (8-OHdG) is a sensitive marker of the DNA damage due to hydroxyl radical attack at the C8 of guanine. This damage, if left unrepaired, has been proposed to contribute to mutagenicity and cancer promotion. We conducted this biomonitoring study with the aim of evaluating the association between excretion of 8-OHdG and level of exposure to benzene and other aromatic compounds among occupationally exposed people. METHODS--A random sample of 65 filling station attendants from Rome, Italy was studied for personal exposure to benzene, toluene, and xylenes, and excretion of 8-OHdG. Information about age, length of employment, smoking habits, and diagnostic exposure to x rays was collected by questionnaire. An average yearly level of exposure to benzene and methylbenzenes was calculated for each filling station attendant on the basis of about seven repeated personal samples collected during one year. A spot sample of 20 ml of urine was collected from each worker. Concentrations of 8-OHdG were determined by high performance liquid chromatography (HPLC) with coupled columns. RESULTS--A mean (SD) concentration of 1.36 (0.49) mumol of 8-OHdG/mol of creatinine was measured. A significant correlation was found between urinary 8-OHdG and exposure to benzene (r = 0.34). In a multiple regression analysis relating the concentration of urinary 8-OHdG with the age, length of employment, smoking, diagnostic exposure to x rays and personal exposure to benzene, an increase of 0.15 mumol/mol creatinine in urinary 8-OHdG/unit increase in the natural logarithm of the average yearly benzene concentration was estimated. CONCLUSION--This study shows a dose-response effect between personal exposure to benzene and urinary 8-OHdG concentration; further studies are needed to clarify the biological significance of 8-OHdG as a marker of cancer risk.